Health and social care systems of the future : demographic changes, digital age and human factors : proceedings of the Healthcare Ergonomics and Patient Safety, HEPS, 3-5 July, 2019 Lisbon, Portugal /: demographic changes, digital age and human factors : proceedings of the Healthcare Ergonomics and Patient Safety, HEPS, 3-5 July, 2019 Lisbon, Portugal. ([2019]) - Unknown
No abstract available